Association of low vitamin D with high disease activity in an Australian systemic lupus erythematosus cohort. Issue 1 (8th April 2015) - Yap, K S; Northcott, M; Hoi, A B-Y; Morand, EF; Nikpour, M
Abstract : Background: Vitamin D status varies with geographic location and no studies of vitamin D in systemic lupus erythematosus (SLE) have been reported in the Southern Hemisphere. Objectives: To assess the prevalence of vitamin D deficiency in an Australian SLE cohort, and its relationship with disease activity. Methods: Data were collected prospectively on 119 consecutive patients with SLE in the Monash Lupus Clinic in Melbourne, Australia, between January 2007 and January 2013. Patients had simultaneous serum 25-hydroxyvitamin D concentration and disease activity (SLEDAI-2K) recorded. Statistical methods were used to determine the correlation of serum vitamin D level and disease activity both at baseline and at a subsequent time point. Adjustments were made for the use of glucocorticoids, immunosuppressants and vitamin D supplementation. Results: Vitamin D deficiency (<40 nmol/L) was detected in 27.7% of patients at baseline. Multiple regression analysis showed a significant inverse correlation of SLEDAI-2K with baseline vitamin D level and with vitamin D supplementation. Over a 12-month period of observation, among the 119 patients, there were 464 serial vitamin D measurements with corresponding SLEDAI-2K, representing 266 time intervals. The median change in vitamin D level was an increase of 25 nmol/L and this corresponded with a decline in SLEDAI-2K of 2 units. In regression analysis, there was a significant association between low vitamin D at a prior time point and a rise in SLEDAI-2K at the subsequent time point (univariable OR 3.3, 95% CI 1.5 to 7.7, p=0.005) or having a high disease activity (SLEDAI-2k>10) at the subsequent time point (univariable OR 3.1, 95% CI 1.4 to 6.8, p=0.004). Conclusions: In Australian patients with SLE, low vitamin D was associated with a higher disease activity and an increase in serum vitamin D was associated with reduced disease activity over time. The therapeutic effect of vitamin D in SLE should be further assessed in interventional studies.